P PROFIL KETERAMPILAN SOSIAL ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH INKLUSIF (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This research is motivated by the importance of social skills in children with special needs in inclusive schools. The purpose of this study was to describe the profile of the social skills of children with special needs in the Inclusive School, namely the Superior State Elementary School, Kuningan Regency. The focus of this research is two children with ADHD and a child who is intellectually and intellectually slow. This study uses a descriptive qualitative approach. Data collection techniques in this study were carried out by means of interviews and questionnaires to teachers and parents of students. The results of interviews with parents showed that n1 and n2 categories of assessment were sufficient, and n3 categories of good assessments.